Peningkatan Kesadaran Masyarakat Terhadap Pengelolaan Sampah RT 57 Kelurahan Graha Indah, Balikpapan - Pratomo, Rahmat Aris; Hasanah, Kharisma Nurul; Putri, Ivana Diva; Puspita, Della Candra; Dewi, Tyara Virnasari; Nisa, Juwita Wulan; Nurdiana, Nurdiana; Dewanda, Rifqi; Sitanggang, Jenius PH; Tufail, Dwiana Novianti (Universitas Pahlawan Tuanku Tambusai, 2024)
Rukun Tetangga (RT) 57 in Graha Indah sub-district is an area that faces waste problems. Based on the results of the initial field observations, the main waste-related problem in the RT 57 Graha Indah area is the lack of awareness of residents in proper waste management. Therefore, an initiative is required to increase the community's awareness of waste management. The provided solution to reduce this problem is the waste bank and composting programme. The method used in this community service is a mentoring method in waste bank activities, including the utilisation of inorganic waste by selling waste to waste collectors to generate revenue and improve the community's economy. In addition, assistance is carried out in the composting programme. As a result of waste bank activities, residents actively collect and sell waste with a total customer fund of IDR 150,000. In the composting programme, after 1 month, the organic composting is ready for use. The results of the programme evaluation also showed that there was an increase in the RT 57 community's understanding of waste management by 42-54%.